A Systematic Framework for Radio Frequency Identification (RFID) Hazard Mitigation in the Blood Transfusion Supply Chain from Donation to Distribution - (:unkn) unknown (My University, 2012)
The RFID Consortium is developing what will be the first FDA-approved use of radio frequency identification (RFID) technology to identify, track, manage, and monitor blood throughout the entire blood transfusion supply chain. The iTraceTM is an innovative technological system designed to optimize the procedures currently employed when tracing blood from the donor to the recipient. With all novel technologies it is essential to consider not only the advantages, but also the potential harms that may come about from using the system. The deployment of the iTraceTM consists of two phases: 1) Phase One - application of the iTraceTM from the donor to blood center distribution, and 2) Phase Two - application of the iTraceTM from blood center distribution to transfusion. This dissertation seeks to identify the possible hazards that may occur when utilizing the iTraceTM during Phase One, and to assess the mitigation and correction processes to combat these hazards. A thorough examination of verification and validation tests, as well as of the system design, requirements, and standard operating procedures was performed to qualify and quantify each hazard into specific categories of severity and likelihood. A traceability matrix was also established to link each hazard with its associated tests and/or features. Furthermore, a series of analyses were conducted to determine whether the benefits of implementing the iTraceTM outweighed the risks and whether the mitigation and correction strategies of the hazards were effective. Ultimately, this dissertation serves as a usable, generalizable framework for the management of RFID-related hazards in the blood transfusion supply chain from donor to blood center distribution.
Keywords: Biomedical and Health Informatics; Blood Transfusion Supply Chain; Hazards; Healthcare Devices; Radio Frequency Identification (RFID); Risk Mitigation